Impact of Peritoneal Interposition Flap on Patients Undergoing Robot-assisted Radical Prostatectomy and Pelvic Lymph Node Dissection: A Systematic Review and Meta-analysis of Randomized Controlled Trials - May, Matthias; Gilfrich, Christian; Bründl, Johannes; Ubrig, Burkhard; Wagner, Joseph R; Gloger, Simon; Student, Vladimir; Merseburger, Axel S; Thomas, Christian; Brookman-May, Sabine D; Wolff, Ingmar (European urology focus, 2024)
CONTEXT: Symptomatic lymphocele (sLC) occurs at a frequency of 2-10% after robot-assisted radical prostatectomy (RARP) with pelvic lymph node dissection (PLND). Construction of bilateral peritoneal interposition flaps (PIFs) subsequent to completion of RARP + PLND has been introduced to reduce the risk of lymphocele, and was initially evaluated on the basis of retrospective studies. OBJECTIVE: To conduct a systematic review and meta-analysis of only randomized controlled trials (RCTs) evaluating the impact of PIF on the rate of sLC (primary endpoint) and of overall lymphocele (oLC) and Clavien-Dindo grade ≥3 complications (secondary endpoints) to provide the best available evidence. EVIDENCE ACQUISITION: In accordance with the Preferred Reporting Items for Meta-Analyses statement for observational studies in epidemiology, a systematic literature search using the MEDLINE (PubMed), Cochrane Central Register of Controlled Trials (CENTRAL), and EMBASE databases up to February 3, 2023 was performed to identify RCTs. The risk of bias (RoB) was assessed using the revised Cochrane RoB tool for randomized trials. Meta-analysis used random-effect models to examine the impact of PIF on the primary and secondary endpoints. EVIDENCE SYNTHESIS: Four RCTs comparing outcomes for patients undergoing RARP + PLND with or without PIF were identified: PIANOFORTE, PerFix, ProLy, and PLUS. PIF was associated with odds ratios of 0.46 (95% confidence interval [CI] 0.23-0.93) for sLC, 0.51 (95% CI 0.38-0.68) for oLC, and 0.41 (95% CI 0.21-0.83) for Clavien-Dindo grade ≥3 complications. Functional impairment resulting from PIF construction was not observed. Heterogeneity was low to moderate, and RoB was low. CONCLUSIONS: PIF should be performed in patients undergoing RARP and simultaneous PLND to prevent or reduce postoperative sLC. PATIENT SUMMARY: A significant proportion of patients undergoing prostate cancer surgery have regional lymph nodes removed. This part of the surgery is associated with a risk of postoperative lymph collections (lymphocele). The risk of lymphocele can be halved via a complication-free surgical modification called a peritoneal interposition flap.
Keywords: Randomized Controlled Trials as Topic; peritoneum; Lymphocele; lymfadenektomie; Peritoneum; Robotic Surgical Procedures; Peritoneal interpolated flap; chirurgické laloky; lidé; Peritoneal rotation flap; Lymph Node Excision; pooperační komplikace; nádory prostaty; Prostatectomy; Surgical Flaps; Prostatic Neoplasms; Pelvis; Systematic review; lymfokela; Pelvic lymphadenectomy; Male; Postoperative Complications; Peritoneal reapproximation; pánev; randomizované kontrolované studie jako téma; prostatektomie; mužské pohlaví; roboticky asistované výkony; Humans